Desired features for a novel stent-graft - Isa C. T. Santos (2012)
Abdominal aortic aneurysms are indolent but deadly. Among the current treatments is endovascular aneurysm repair, a minimally invasive procedure that resorts to a stent-graft to shield the aortic wall from blood pressure. Although this procedure allowed more patients to be treated and offers several other advantages, complications still occur and there is a need for a more efficient stent-graft. Here, the early steps performed in the development of a novel stent-graft are described, and desired features for an "ideal" device are pointed out. The implementation of these characteristics will lead to a more efficient medical device.